Analyzing International Students’ Study Anxiety in Higher Education - Khoshlessan, Rezvan; Das, Kumer Pial (Journal of International Students, 2017)
The purpose of this study is to explore international students’ study anxiety in a mid-sized public four-year university in Southeast Texas by comparing their existing study anxiety along lines of nationality, gender, age, major, degree, and stage of education. The subjects were selected using a convenience sample during the Spring of 2013. The researcher collected pertinent demographic data and used a modified version of the Study Anxiety Questionnaire (SAQ). The non-parametric statistical analysis focuses on the students’ perceptions and the study anxiety of international students which has been grouped into five anxiety subgroups. The results demonstrate some differences in anxiety levels among different demographic groups.